Understanding Organizational Psychology: Key Concepts and Applications - Kessi, Andi Muhammad Fara; Sumarni, Sumarni (Fakultas Ekonomi, Universitas Muslim Indonesia, 2023)
This study aims to explore how organizational psychology principles—specifically motivation, leadership, and organizational culture—can be practically applied to enhance organizational performance. A comprehensive qualitative analysis was conducted through a systematic literature review. The study integrates classical and contemporary theories with empirical case studies to understand the interplay between intrinsic and extrinsic motivators, leadership styles, and cultural attributes. The findings reveal that intrinsic motivators, such as autonomy and personal growth, significantly enhance long-term employee engagement and productivity, while extrinsic motivators, though effective short-term, can undermine intrinsic interest if overemphasized. Transformational leadership fosters positive organizational cultures and drives innovation, contrasting with transactional leadership, which is effective in stable environments. Organizational culture profoundly influences ethical behavior and decision-making. Organizations should adopt a balanced approach integrating both intrinsic and extrinsic motivators, develop transformational leadership capabilities, and foster an ethical culture to sustain effectiveness and innovation. These strategies align psychological principles with practical organizational needs, helping to navigate the complexities of modern work environments.